DETERMINANTS OF ENTERPRISES LIFE CYCLE IN MODERN CONDITIONS OF DEVELOPMENT - Polyanska , A.S. (The actual problems of regional economy development, 2016)
In the article the theoretical basis of organization life cycle research as well as the particularly of the organization life cycle concept implementation for solving of modern targets of enterprises and organizations development are highlighted. The determinants of one life cycle stage transformation to the other at the enterprises, that allows to better understand the conditions of its functioning and to identify factors that affect the viability of the company and its duration, are considered. Management technologies at different stages of organizations life cycle are proposed. JEL: M 20